Оn reconstruction of the service and life of the church priests of the Caucasus region in the first half of the XIX century - Yu. Yu. Grankin; Yu. Yu. Klychnikov; S. S. Lazaryan (Гуманитарные и юридические исследования)
The clergy of the North Caucasus were a specific and small group of the population of the region, on whose shoulders the Church and the State were entrusted with very important and significant official tasks in terms of coverage and depth of influence on the minds of people. Together with the word of God, they had to bring the light of enlightenment, change the forms of community life and transform the mores that reigned in the region, in which violence and trampling of human life was almost commonplace. At the same time, they were charged not only to free their hearts from filth and hatred, not only to instruct and guide people to the truth, but to inspire love for the imperial fatherland, as well as obedience and respect for the imperial authorities.The life and ministry of these people took place in difficult conditions of developing natural-climatic or social cataclysms that plunged the population into a state of uncertainty or fear. Many and everyday threats demanded great endurance, self-control, and sometimes heroism from the clergy in order to remain true to their chosen destiny. These people were involved in everyday events unfolding in the region, participated in interethnic communications, acted as peacekeepers, and helped the offended and suffering. At the same time, along with everyone, they were exposed to the dangers of wartime, died at the hands of villains or mountain riders, hostile to Russians, died at their post, healing and comforting the settlers in Cossack villages and villages during frequent epidemic diseases in the region in the first half of the 19th century.A lot of work was brought by the clergy to convert people of heterodox confessions and even criminals to the Christian faith, saving their souls and returning people to the world to continue their creative existence.